2019
DOI: 10.1128/cmr.00111-18
|View full text |Cite
|
Sign up to set email alerts
|

Candida parapsilosis: from Genes to the Bedside

Abstract: SUMMARY Patients with suppressed immunity are at the highest risk for hospital-acquired infections. Among these, invasive candidiasis is the most prevalent systemic fungal nosocomial infection. Over recent decades, the combined prevalence of non-albicans Candida species outranked Candida albicans infections in several geographical regions worldwide, highlighting the need to understand their pathobiology in order to develop effective treatment and to prevent future outbreaks. Candida parapsilosis is the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
235
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(269 citation statements)
references
References 379 publications
(460 reference statements)
10
235
0
2
Order By: Relevance
“…To fill in this gap, we here undertook a transcriptomic analysis of two independently formed hybrid strains from the emerging yeast pathogen Candida orthopsilosis (Pryszcz et al 2014; Schröder et al 2016). This yeast belongs to the CTG clade and is phylogenetically placed within the C. parapsilosis sensu lato species complex alongside with the other opportunistic pathogens C. parapsilosis (Pammi et al 2013; Tóth et al 2019) and C. metapsilosis (Tavanti et al 2005). It has been shown that most (~93%) of the clinical isolates of C. orthopsilosis are hybrids between parentals with ~5.1% nucleotide divergence.…”
Section: Introductionmentioning
confidence: 99%
“…To fill in this gap, we here undertook a transcriptomic analysis of two independently formed hybrid strains from the emerging yeast pathogen Candida orthopsilosis (Pryszcz et al 2014; Schröder et al 2016). This yeast belongs to the CTG clade and is phylogenetically placed within the C. parapsilosis sensu lato species complex alongside with the other opportunistic pathogens C. parapsilosis (Pammi et al 2013; Tóth et al 2019) and C. metapsilosis (Tavanti et al 2005). It has been shown that most (~93%) of the clinical isolates of C. orthopsilosis are hybrids between parentals with ~5.1% nucleotide divergence.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of nosocomial infections caused by Candida has risen significantly in recent decades. Among this genus, C. parapsilosis is the species that has most notably increased in incidence, causing 10%‐25% of candidaemias in neonates and patients in intensive care units 5,17,24 . Candida parapsilosis infections are associated with the use of medical devices, such as central venous catheters, parenteral nutrition administration and healthcare worker contact 5,25‐28 .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of invasive candidiasis has increased in recent decades, and Candida parapsilosis is a notable species of Candida . Depending on the geographical area, C. parapsilosis is the second most frequently isolated species, and in some hospitals in Europe, Asia and South America, it has even overtaken Candida albicans in incidence 1‐6 . C. parapsilosis infection predominates in low‐weight neonates, critically ill patients or those with cancer and is associated with the disruption of anatomical barriers by invasive procedures, such as central venous catheter placement, surgery and parenteral nutrition administration 3,5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations